2015
DOI: 10.1177/0269881115575536
|View full text |Cite
|
Sign up to set email alerts
|

The role of distress intolerance for panic and nicotine withdrawal symptoms during a biological challenge

Abstract: Anxious responding in response to stressful experiences may explain the impact of perceived distress intolerance on panic and nicotine withdrawal symptom expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…This is consistent with the finding that female users, relative to male, had shorter average breath-holding durations at baseline and following both drug conditions. These findings contribute to the growing literature that document sex differences in perceived distress intolerance (e.g., Johnson, Berenz, & Zvolensky, 2012; Simons & Gaher, 2005) and breath-holding duration in community-recruited samples with and without psychopathology (Johnson et al, 2012), trauma-exposed individuals (Berenz et al, 2012) and substance using populations, including cigarette smokers (Hogan et al, 2015; Farris, Zvolensky, Otto, & Leyro, 2015; Perkins, Geidgowd, Karelitz, Conklin, & Lerman, 2012) and smokers who are also heavy drinkers (Kahler et al, 2015). This sex-difference has also been found in other behavioral distress intolerance tasks among cigarette smokers (e.g., persistence during a carbon-dioxide challenge; Brown et al, 2002).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This is consistent with the finding that female users, relative to male, had shorter average breath-holding durations at baseline and following both drug conditions. These findings contribute to the growing literature that document sex differences in perceived distress intolerance (e.g., Johnson, Berenz, & Zvolensky, 2012; Simons & Gaher, 2005) and breath-holding duration in community-recruited samples with and without psychopathology (Johnson et al, 2012), trauma-exposed individuals (Berenz et al, 2012) and substance using populations, including cigarette smokers (Hogan et al, 2015; Farris, Zvolensky, Otto, & Leyro, 2015; Perkins, Geidgowd, Karelitz, Conklin, & Lerman, 2012) and smokers who are also heavy drinkers (Kahler et al, 2015). This sex-difference has also been found in other behavioral distress intolerance tasks among cigarette smokers (e.g., persistence during a carbon-dioxide challenge; Brown et al, 2002).…”
Section: Discussionmentioning
confidence: 56%
“…In concert, given the consistent evidence that distress intolerance is linked to various forms of psychopathology, including the maintenance of problematic substance use (Leyro et al, 2010), these data have the potential to uniquely inform the nature of affective symptoms following acute cannabis use. Specifically, given distress intolerance is linked to heightened physiological/subjective distress and emotional reactivity (Farris et al, 2015; Marshall et al, 2008), following cannabis use, increases in distress intolerance may promote emotion-focused coping (e.g., Bujarski et al, 2012), which may in turn result in re-initiation of cannabis use (Hasan, Babson, Banducci, & Bonn-Miller, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…For example, prior literature has found that distress intolerance may only be linked to nicotine withdrawal symptoms severity and risk for smoking lapse when considered in the context of negative affect (Abrantes et al, 2008; Farris et al, 2015). We did not statistically model ‘distress states’ in relation to distress intolerance (e.g., an interaction effect) in the current study; however, discomfort intolerance was examined during a smoking cessation attempt, which has been conceptualized as a critical ‘window’ for experiencing acute distress (Shiffman, West, & Gilbert, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when given the opportunity to smoke, these individuals may be distress avoidant and report lower urges to smoke and evidence attenuated puffing behavior. To date, we are aware of only two studies that have examined the role of anxious arousal on smoking craving (Attwood et al, 2014) and subjective nicotine withdrawal symptom severity (Farris et al, 2015c), whereas other investigations have exclusively focused on explicating the nature of anxious responding to physiological provocation among smokers versus non-smokers (Abrams et al, 2008b), or among smokers in nicotine deprivation or not (Abrams et al, 2011;Leyro and Zvolensky, 2013;Vujanovic and Zvolensky, 2009). Of note, these studies have not modeled acute anxious arousal, as they have utilized lower concentrations of carbon dioxide (CO 2 ) gas for a longer duration which produces prolonged and lower-intensity arousal (Abrams et al, 2008a).…”
mentioning
confidence: 99%